Solvothermal synthesis, sintering behavior and dielectric properties of potassium niobate fine powders - Kittichai Jinachai (2018)
Fine potassium niobate powders composing of sub-micrometer sized lumber particles were synthesized under solvothermal conditions, with the use of mixed water-ethyl alcohol as the reaction medium and the application of the prior ultrasonication as the activation step. The influences of ethyl alcohol on particle shape and size, and the prior ultrasonication on the sintering behavior of the synthesized powders are present and discussed in relative to the conventional hydrothermal cases. The temperature dependent dielectric constants (εr) and dielectric losses (tan δ) of the sintered ceramics are also included, showing the origin of the losses to stem from the loss of potassium oxide in the sintering process.